Good night, Little Blue Truck - Schertle, Alice (Houghton Mifflin Harcourt, 2019)
A storm is brewing and Little Blue Truck and his good friend Toad are hurrying home for bed. But who can sleep with all that racket? It's not long before other friends show up seeking safety from the storm. Thunder and lightening sure can be scary, but it's easy to be brave together. When the clouds roll on and the sky is clear, it's all aboard for a bedtime ride! Beep! Beep! Shhh.